KARAKTERISTIK TIPE PENGAMBILAN KEPUTUSAN ANGGARAN KEPALA SEKOLAH - Trisharsiwi Trisharsiwi; Wachid Pratomo (Universitas Sarjanawiyata Tamansiswa, 2020)
This study set a goal to describe the characteristics types of educational budget decision making in Taman Muda Ibu Pawiyatan Tamansiswa Yogyakarta. The research was carried out over six months with research subjects: the Chairperson of the Ibu Pawiyatan Board, the Chairperson of the Taman Muda Ibu Pawiyatan Division, Teachers in the Taman Muda Ibu Pawiyatan, the treasury division, several staffs involved in the budgeting, parents involved in seeking funding sources, and people who were always critical in every decision making and budgeting, both at the level of the Mother Pawiyatan Board or in the Taman Muda Ibu Pawiyatan Division. Research data were collected using in-depth interviews, observation, and documentation. The research data were analyzed using the Huberman and Miles version of the data analysis technique consisting of data reduction, data presentation, and concluding. The results showed that the characteristics of the decision making type in the principal's education budget are situational, sometimes using his authority, but in certain situations involving the subordinates’ point of view democratically.